Binge eating disorder and morbid obesity are associated with lowered mu-opioid receptor availability in the brain - Juho Joutsa; Henry K. Karlsson; Joonas Majuri; Pirjo Nuutila; Semi Helin; Valtteri Kaasinen; Lauri Nummenmaa (ELSEVIER IRELAND LTD, 2022)
Both morbid obesity and binge eating disorder (BED) have previously been linked with aberrant brain opioid function. Behaviorally these two conditions are however different suggesting also differences in neurotransmitter function. Here we directly compared mu-opioid receptor (MOR) availability between morbidly obese and BED subjects. Seven BED and nineteen morbidly obese (non-BED) patients, and thirty matched control subjects underwent positron emission tomography (PET) with MOR-specific ligand [C-11]carfentanil. Both subjects with morbid obesity and BED had widespread reduction in [C-11]carfentanil binding compared to control subjects. However, there was no significant difference in brain MOR binding between subjects with morbid obesity and BED. Thus, our results indicate that there is common brain opioid abnormally in behaviorally different eating disorders involving obesity.